2014
DOI: 10.17269/cjph.105.4608
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, lifestyle and socio-economic determinants of vitamin D intake: A population-based study of Canadian children

Abstract: OBJECTIVE: Vitamin D intake in childhood is primarily for the prevention of rickets. Inconsistent evidence has associated adequate blood concentrations with a decreased risk of certain health conditions. Further, obese individuals may have lower vitamin D status. The estimated average requirement (EAR) for children recently doubled to 400 IU/day. Our aim was to examine dietary intake of vitamin D in different body mass index (BMI) categories, in addition to assessing determinants. METHODS:Data from two provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…The vitamin D intake of children in some Canadian provinces is below the current EAR and RDA ( 23 , 24 ) . However, national data from the Canadian Health Measures Survey (CHMS) indicates that most children are vitamin D sufficient, considering that the average vitamin D concentration of children aged 6–11 years was 75 nmol/l in 2007–2009 and 67 nmol/l in 2009–2011 ( 12 , 25 ) .…”
mentioning
confidence: 95%
“…The vitamin D intake of children in some Canadian provinces is below the current EAR and RDA ( 23 , 24 ) . However, national data from the Canadian Health Measures Survey (CHMS) indicates that most children are vitamin D sufficient, considering that the average vitamin D concentration of children aged 6–11 years was 75 nmol/l in 2007–2009 and 67 nmol/l in 2009–2011 ( 12 , 25 ) .…”
mentioning
confidence: 95%
“…An increased adherence to vitamin D and calcium supplements in the present study was more likely in women who more often attended antenatal care, where they received supplements. Some previous studies found that high household income and education were strongly associated with increased vitamin intake from food [ 4 ]. Although this difference was not observed in the present study, we found that women with a high household income (≥15000 SR) were more likely to consume vitamin D supplements than women with a low household income (<15000 SR) (47.2% versus 32.2%, p =0.02), which may explain the higher serum 25(OH) D concentrations that were found in women with high household income compared to those with low household income (median 25(OH) D: 38.1 nmol/L versus 33.2 nmol/L, p =0.035).…”
Section: Discussionmentioning
confidence: 99%
“…Sunlight exposure, rather than diet, has been reported as the main source of vitamin D for the majority of the population [ 1 , 2 ]. However, sun exposure has become a less viable source of vitamin D due to widespread use of sunscreen and a more sedentary indoor lifestyle [ 4 ] and for certain populations with limited sunlight exposure, such as veiled women [ 5 ]. Limited exposure to sunlight has consistently been identified as a main contributing factor for vitamin D deficiency (serum hydroxyvitamin D 25(OH) D < 50 nmol/L) in Saudi Arabia, particularly in women because the traditional clothing covers most of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Saudi Arabia reports some of the world’s highest rates of vitamin D deficiency [ 6 – 8 ], with Saudi women at a particularly high risk [ 9 , 10 ]. In our recent national study [ 11 ], we confirmed that vitamin D deficiency is highly prevalent (77.6%) among premenopausal Saudi women.…”
Section: Introductionmentioning
confidence: 99%